Testing of badminton-specific endurance - Madsen, C. M.; Højlyng, M.; Nybo, L. (The Journal of Strength and Conditioning Research, 2016)
In the present study, a novel intermittent badminton endurance (B-ENDURANCE) test was developed and tested in elite (n = 17) and skilled (n = 9) badminton players and in age-matched physically active men (nonbadminton players; n = 8). In addition, B-ENDURANCE test-retest reproducibility was evaluated in 9 badminton players. The B-ENDURANCE test is an incremental test where each level consists of repeated sequences of badminton-specific actions toward the 4 corners of the court. The subject starts in the center of the court in front of a computer screen and within each sequence, he must, in a randomized order, complete 8 actions as dictated by the computer, providing the audiovisual input and verifying that the appropriate sensor is activated within the allocated time. Recovery time between each sequence is 10 seconds throughout the test, but the time to complete each sequence is gradually decreased until the subjects cannot follow the dictated tempo. The B-ENDURANCE test performance for elite players was better (p = 0.05) compared with the skilled players and nonbadminton players. In addition, the B-ENDURANCE test performance correlated (r = 0.8 and p < 0.0001) with elite players' national single rankings. Test-retest coefficient of variation was 7.9% between the first 2 trials (i.e., without a familiarization trial) but reduced to 2.5% when comparing the second and third trials. In conclusion, the B-ENDURANCE test is relevant for the evaluation of badminton-specific endurance but at least 1 familiarization trial is recommended if the test is used for evaluation of longitudinal changes, e.g., tracking training effects.